2014
DOI: 10.2341/13-070-lit
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resin Cement on Bond Strength of Glass-fiber Posts Luted Into Root Canals: A Systematic Review and Meta-analysis of In Vitro Studies

Abstract: Because there are several ways to cement glass-fiber posts (GFPs) into root canals, there is no consensus on the best strategy to achieve high bond strengths. A systematic review was conducted to determine if there is difference in bond strength to dentin between regular and self-adhesive resin cements and to verify the influence of several variables on the retention of GFPs. This report followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. In vitro studies that investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
2
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(204 citation statements)
references
References 31 publications
4
182
2
16
Order By: Relevance
“…The risk of bias evaluation was based on and adapted from a previous study (Sarkis-Onofre et al, 2014) and evaluated according to the description of the following parameters for the study's quality assessment: randomization of teeth, use of teeth free of caries or restoration, materials used according to the manufacturer's instructions, adhesive procedures performed by the same operator, description of sample size calculation, and blinding of the operator of the testing machine. If the authors reported the parameter, the paper had a Y (yes) on that specific parameter; if it was not possible to find the information, the paper received an N (no).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
“…The risk of bias evaluation was based on and adapted from a previous study (Sarkis-Onofre et al, 2014) and evaluated according to the description of the following parameters for the study's quality assessment: randomization of teeth, use of teeth free of caries or restoration, materials used according to the manufacturer's instructions, adhesive procedures performed by the same operator, description of sample size calculation, and blinding of the operator of the testing machine. If the authors reported the parameter, the paper had a Y (yes) on that specific parameter; if it was not possible to find the information, the paper received an N (no).…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
“…Moreover, water is then reused via a reaction with functional acid groups, and also during the reaction of the cement, resulting in a hydrophobic matrix. The bond obtained relies upon the micro-mechanical retention and chemical interaction between the acid monomer and hydroxyapatite groups 4,21 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of in vitro studies showed that SARC use could improve the retention of GFPs into root canals [26]. Furthermore, self-adhesive cements have demonstrated clinical outcomes similar to conventional multi-step cementation procedures [27,28].…”
Section: Resultsmentioning
confidence: 99%